Household energy consumption in Henan province: Current status, challenges, and optimized development pathways - Lin, Li; Babatunde, Kazeem Alasinrin; Talib, Zunirah Mohd (Edelweiss Applied Science and Technology, 2024)
Energy consumption serves as a critical link between economic development and ecological protection, and it is one of the key pathways to achieving the "dual carbon" goals. As the most populous province in China, Henan's household energy consumption holds a significant position in the country's overall energy usage, making it a region of notable representativeness and research value. This paper examines the temporal evolution and spatial distribution characteristics of household energy consumption in Henan Province, systematically analyzing the major challenges encountered in its transition toward clean energy, and proposes optimized development pathways. The study finds that while the total household energy consumption in Henan Province has continued to grow in recent years, its growth rate has gradually slowed. The energy structure has shown a trend toward cleaner energy, with the proportion of electricity and natural gas usage increasing significantly. However, challenges such as uneven development of regional energy infrastructure, insufficient adoption of clean energy, low energy efficiency, and weak public awareness of green consumption remain prominent, hindering the modernization and clean energy transition of household energy consumption. To address these challenges, this paper recommends optimizing regional energy infrastructure, strengthening policy support for clean energy, promoting efficient and energy-saving equipment, improving household energy efficiency, and popularizing green energy consumption concepts. These measures aim to accelerate the transition of household energy consumption in Henan Province toward modernization and cleaner energy. The findings not only provide a scientific basis for optimizing Henan's household energy structure but also offer valuable insights for energy transitions in other regions across China.